GASKAP-The Galactic ASKAP Survey - Dickey, J.; McClure-Griffiths, N.; Gibson, S.; Gómez, J.; Imai, H.; Jones, P.; Stanimirovic, S.; Van Loon, J.; Walsh, Andrew; Alberdi, A.; Anglada, G.; Uscanga, L.; et al. (CSIRO, 2013)
A survey of the Milky Way disk and the Magellanic System at the wavelengths of the 21-cm atomic hydrogen (H i) line and three 18-cm lines of the OH molecule will be carried out with the Australian Square Kilometre Array Pathfinder telescope. The survey will study the distribution of H i emission and absorption with unprecedented angular and velocity resolution, as well as molecular line thermal emission, absorption, and maser lines. The area to be covered includes the Galactic plane (|b| < 10°) at all declinations south of d = +40°, spanning longitudes 167° through 360°to 79° at b = 0°, plus the entire area of the Magellanic Stream and Clouds, a total of 13 020 deg2. The brightness temperature sensitivity will be very good, typically sT? 1 K at resolution 30 arcsec and 1 km s-1. The survey has a wide spectrum of scientific goals, from studies of galaxy evolution to star formation, with particular contributions to understanding stellar wind kinematics, the thermal phases of the interstellar medium, the interaction between gas in the disk and halo, and the dynamical and thermal states of gas at various positions along the Magellanic Stream.